1990
DOI: 10.2466/pms.1990.70.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Physical Activity on Concentration among Junior High-School Students

Abstract: The level and quality of concentration were tested before and after each lesson in one class session. Two of the four classes participated in physical education activities, and the other two studied science. Each subject matter was studied the beginning and at the end of the school day. The research design was 2 x 2 x 2 factorial (two subject matters, two times of the school day, and as a repeated measure two times of test for each group at the beginning and end of each lesson). The level and the quality of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 5 publications
1
40
0
2
Order By: Relevance
“…10 Improvements after exercise have been reported in three studies of performance on speeded arithmetic tasks before and after physical activity, but these studies all lacked adequate control conditions for practice. [14][15][16] Improvements in concentration after physical exercise, assessed using visual search tasks, have been reported in three further studies, [17][18][19] but again these findings may be better explained by practice effects 19 or uncontrolled between-group variance. 17,18 We sought to address the lack of research in this area by conducting a pilot study of the effects of physical exercise on psychometric tests, which would bear ecological validity in relationship to classroom performance.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…10 Improvements after exercise have been reported in three studies of performance on speeded arithmetic tasks before and after physical activity, but these studies all lacked adequate control conditions for practice. [14][15][16] Improvements in concentration after physical exercise, assessed using visual search tasks, have been reported in three further studies, [17][18][19] but again these findings may be better explained by practice effects 19 or uncontrolled between-group variance. 17,18 We sought to address the lack of research in this area by conducting a pilot study of the effects of physical exercise on psychometric tests, which would bear ecological validity in relationship to classroom performance.…”
mentioning
confidence: 95%
“…[14][15][16] Improvements in concentration after physical exercise, assessed using visual search tasks, have been reported in three further studies, [17][18][19] but again these findings may be better explained by practice effects 19 or uncontrolled between-group variance. 17,18 We sought to address the lack of research in this area by conducting a pilot study of the effects of physical exercise on psychometric tests, which would bear ecological validity in relationship to classroom performance. To address previous methodological issues we used a crossover, counterbalanced, within-participant study design that controlled for all factors other than age and classroom physical exercise.…”
mentioning
confidence: 98%
“…In contrast to these findings, it has also been reported that attention (as assessed by the d2 test of attention) was not affected following a physical education lesson (when compared to following a science lesson) (24), nor was performance on the Stroop test enhanced following a mid-morning bout of exercise in adolescents (9).…”
Section: 1: Stroop Testmentioning
confidence: 76%
“…Given the fact that students start their school day from early morning to afternoon, students are engaging in several instructional academic lessons for roughly 6-7 hours of the school time. It was evidenced that students' attention and concentration were lower late in the school day compared to early in the school day [18].…”
Section: Introductionmentioning
confidence: 99%
“…School teachers often claim that the last two class periods of the school day were the most challenging for them to gain students' attention to their instructions and to motivate them stay focused on the task engagement and performance [18]. To solve this imperative issue, there is a critical need to develop feasibly implemented intervention strategies that increase students' attention and concentration late in the school day.…”
Section: Introductionmentioning
confidence: 99%